Exome Sequencing Identifies Patterns of Disruptive Mutations in Oropharyngeal Squamous Cell Carcinoma. (23rd August 2013) - Janus, Jeffrey R.; Laborde, Rebecca R.; Olsen, Steven; Olsen, Kerry D.; Moore, Eric J.; Kasperbauer, Jan L.; Smith, David
Abstract : Objectives: 1) Describe the frequency of disruptive gene mutations in current or never smoking patients. 2) Analyze coding regions to identify tumor specific nonsense mutations in genes related to tumor development and critical signaling pathways. Methods: Tumor and adjacent normal oropharyngeal mucosal samples were obtained from 8 patients undergoing surgical treatment of oropharyngeal squamous cell carcinoma (OPSCC) from 2010‐2012 representing HPV positive current and never smoking groups. Next generation sequencing following exome enrichment was performed to identify various classes of variants from each sample. Comparative analysis was conducted using Genesifter from PerkinElmer. Results: A global analysis of all mutation types determined that tumor tissues from current smoking patients contain 20% more missense mutations than never smoking groups, resulting in an amino acid substitution. Current smoking patients have tumor specific nonsense mutations in coding regions enriched for tumor suppressor genes and displayed extensive evidence of identical mutation in tumor and adjacent normal tissue. Never smoking patients have a greater number of tumor specific mutations that enrich for genes related to immune system function. Conclusions: Gene mutations that result in truncated proteins are known to associate with cancer development. We have identified a panel of nonsense mutations in current smoking patients that represent tumor suppressor and cell cycle regulatory genes. This group also shows extensive evidence of field cancerization. Never smoking patients carry larger numbers of tumor specific mutations than enrich for genes related to immune system regulation. This may reflect the involvement of active HPV infection in this group.